Relationship Between Dug Well Construction and Physical Quality of Clean Water in Kayangan, North Lombok - Husnul Hatimah; Iwan Desimal; Yeni Puspita; Muhammad Fauzi Zulkarnaen (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Dug wells serve as the main household water source for communities in the Kayangan Health Center area of North Lombok, making their structural integrity essential for ensuring safe water access. This study aimed to examine the relationship between dug well construction and the physical quality of clean water. An observational analytic study with a cross-sectional design was conducted from April to June 2024. From a total population of 82 dug wells, 45 wells were selected as study samples using the Slovin formula with a 10% margin of error and simple random sampling to ensure equal selection probability. Well construction characteristics were assessed through direct field observation using a structured checklist based on Indonesian Ministry of Health standards. Physical water quality was evaluated through organoleptic testing of color, odor, and taste in accordance with national clean water regulations. The results showed that 88.9% of dug wells did not meet recommended construction requirements, particularly regarding parapet height, well lining, and watertight flooring. Physical testing indicated that 80% of water samples met quality standards, while 20% failed to meet one or more indicators. Statistical analysis using the Chi-Square test revealed no significant association between well construction and physical water quality (p = 0.258). These findings suggest that physical indicators alone may not adequately reflect contamination risks, highlighting the need for comprehensive water quality monitoring that includes microbiological and chemical assessments to ensure groundwater safety.